Book Review: ???Aspek Hukum Perlindungan Anak dan Sistem Pencatatan Kelahiran - Inas Sofia Latif (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2023)
This book was written by Dr. Haznah Aziz, S.H., M.H., a lecturer in the Master of Law Postgraduate Program, Syekh-Yusuf Islamic University, Tangerang. In addition to teaching, he is also active in various research and writing activities, both in the form of articles and books. The majority of his papers discuss legal protection of children, as we can see in his Google Scholar profile. The author actively writes articles in several nationally and internationally accredited journals. This book on Legal Aspects of Child Protection and Birth Registration System is one of the results of his thoughts in the field of Child Protection Law.